Comparison of The HARKIT Score with The STS Score in Predicting Mortality Rates Post Valve Surgery - Ainil Wardah Lubis; Andika Sitepu; Tengku Kemala Intan; Ika Citra Dewi Tanjung (Majalah Kardiologi Indonesia)
Background: Valvular heart disease is a major contributor to increased mortality. The HARKIT score has been validated to predict mortality after specific valve surgery and the STS score to predict mortality rates in patients after cardiac surgery. Haji Adam Malik General Hospital Medan has never used the HARKIT score and the STS score to predict mortality in patients with post valve surgery.